Emerging Trends in Kerala‟s Responsible Tourism. - Shyamala.M , Vidhu.V.L. , Vijesh Venugopal, Deepthi.I (IOSR Journal of Business and Management, 2014)
Discussing On Environmental Matters, Rt Implements Revolutionary Studies And Surveys In The Basic Details Of Energy, Water And Waste And Systematically Reveals A Detailed Energy Audit Analysis Among The Partnering Hotels At 4 Destinations. This Is Expected To Enter To Next Levels Of Preparing Customized Prescriptions For Individual Properties With A Conservation Focus. Responsible Tourism Cell In Destinations Move Against The Negative Impacts Affecting The Environment And Promotes Eco-Friendly Products. Within The Initial Phase, Rt Initiatives In Kerala Become A Replicable Model For The World. There Is A Wide Scope For The Initiative In Tourism Contributing And Benefiting The Local Community While Moving Towards Next Levels With Possible Expansions. The Experiments And Best Stories Of Initial Period Render How Kerala Is Suited In Taking Such A Move Forward